Current Psychotropic Medication Use and Contributing Factors Among Nursing Home Residents With Cognitive Impairment. (January 2021) - Resnick, Barbara; Kolanowski, Ann; Van Haitsma, Kimberly; Galik, Elizabeth; Boltz, Marie; Ellis, Jeanette; Behrens, Liza; Eshraghi, Karen; Zhu, Shijun
This study described current use and predictors of psychotropics among residents with moderate to severe cognitive impairment. This was a secondary data analysis using baseline data from the first 341 residents in an ongoing trial. Predictive measures included age, gender, race, depressive symptoms, agitation, resistiveness to care, depression, cognition, pain, comorbidities, facility factors, and state. Overall 63% ( n = 211) received at least one psychotropic medication, 16% ( n = 52) an anti-seizure medication, 23% ( n = 77) an anxiolytic, 30% ( n = 99) an antidepressant, 2% ( n = 8) a sedative hypnotic, 28% ( n = 93) an antipsychotic medication, and 9% ( n = 29) an opioid. Testing of models explained 9% to 15% of psychotropic medication use. There were high rates of psychotropic medication use and a limited association between demographic factors, behavioral symptoms, and psychotropic medication use. Continued research is needed to explore the impact of deprescribing, person-centered behavioral interventions, and beliefs of providers on psychotropic medication use.